Brazilian Evidence on Tax Evasion and Enforcement: A Case Study of Global North–South Comparison - Clemente, Felippe (Criminal justice review, 2021)
This study investigates the differences observed in the rate of tax evasion between the Global North and South countries, with special focus on Brazil, by comparing key parameters of their tax systems, namely, tax burden, audit cost, and fines. This is achieved by extending and applying Graetz, Reinganun, and Wilde’s model using data from tax authorities from European and Latin American countries, which produced parameters that are used for Bayesian games. The results show that tax evasion is directly associated with tax burden and audit cost, but the effect of fines is unclear. Overall, findings pointed to shortcomings in the tax system of Latin American countries that create the avenue for high tax evasion.